2018
DOI: 10.1038/s41929-018-0081-x
|View full text |Cite
|
Sign up to set email alerts
|

Iron-catalysed substrate-directed Suzuki biaryl cross-coupling

Abstract: Iron-catalysed substrate-directed Suzuki biaryl cross-coupling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
43
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 59 publications
7
43
0
Order By: Relevance
“…A radical mechanism was proposed due to inhibition of the coupling process in the presence of radical scavenger (TEMPO, Table 1, entry 26). 105 Interestingly, this result would suggest radical activation of the aryl─Cl bond and subsequent formation of Csp2-centred radicals, as reported for related cobalt-catalysed systems. 112 iv) Other systems Fürstner and co-workers reported the reactivity of low-valent iron(-II) ferrate ([Fe -II (η 2 -C2H4)4][Li(tmeda)]2) in aryl-alkyl crosscouplings (Table 1, Entry 27).…”
Section: Ii) Systems Involving N-ligandssupporting
confidence: 55%
“…A radical mechanism was proposed due to inhibition of the coupling process in the presence of radical scavenger (TEMPO, Table 1, entry 26). 105 Interestingly, this result would suggest radical activation of the aryl─Cl bond and subsequent formation of Csp2-centred radicals, as reported for related cobalt-catalysed systems. 112 iv) Other systems Fürstner and co-workers reported the reactivity of low-valent iron(-II) ferrate ([Fe -II (η 2 -C2H4)4][Li(tmeda)]2) in aryl-alkyl crosscouplings (Table 1, Entry 27).…”
Section: Ii) Systems Involving N-ligandssupporting
confidence: 55%
“…The activity of iron catalysts in diverse cross-coupling reactions can be controlled via the ligands, for example bis(imino)pyridine 8) or N-heterocyclic carbenes 9) .…”
Section: Ligands In Cross-couplingsmentioning
confidence: 99%
“…Palladium catalysts have traditionally been ubiquitous in cross-coupling reactions. Utilizing iron for the Suzuki coupling to provide simple biaryl compounds remained elusive until recently, when the group of Bedford showed that simple π-coordinating N-pyrrole amides on the aryl halide substrate could facilitate activation of the relatively unreactive C-X bond (Scheme 18) [48]. The use of an NHC ligand with the appropriate steric bulk proved crucial.…”
Section: Cross-coupling Reactionsmentioning
confidence: 99%